Navio de emigrantes de Lasar Segall: uma visão da arte dentro da diáspora - Agostinho, Júlia Marino (2011)
The objective of this essay is to understand the social-historical aspect of the work of art Navio de Emigrantes [Ship of Emigrants] by Lasar Segall, an artist born in Vilnius, Lithuania, naturalized Brazilian citizen. The work of art, besides showing its power, as it is impossible to determine an artistic line due to its being always contemporaneous, allow us a visual and material contact with our own selves. Thus, as we cannot be detached from it, this dissertation presents and discusses the intrinsic relationship between art and society, based on a frame constructed through a contemporaneous fact: the Diaspora